Stem cell proliferation during in vitro development of the model cestode Mesocestoides corti from larva to adult worm - Castillo Estela; Kun Alejandra; Marín Mónica; Domínguez María F; Koziol Uriel (Frontiers in Zoology, 2010)
Abstract Background In free-living flatworms somatic differentiated cells do not divide, and a separate population of stem cells (called neoblasts) is responsible for cell proliferation and renewal. In cestodes, there is evidence that similar mechanisms of cell renewal exist. Results In this work, we have characterized proliferative cells during the development of the model cestode Mesocestoides corti from larva (tetrathyridium) to young segmented worm. This was done by two complementary strategies with congruent results: characterizing cells in S phase and their progeny by incorporation of 5-bromo-2'-deoxyuridine, and characterizing cells in M phase by arresting mitotic cells with colchicine and studying their morphology and distribution. Proliferative cells are localized only in the inner parenchyma, particularly in close proximity to the inner muscle layer, but not in the cortical parenchyma nor in the sub-tegumental tissue. After proliferation some of these cells migrate to the outer regions were they differentiate. In the larvae, proliferative cells are more abundant in the anterior regions (scolex and neck), and their number diminishes in an antero-posterior way. During the development of adult segments periodic accumulation of proliferative cells are observed, including a central mass of cells that constitutes the genital primordium, which grows at least in part due to in situ proliferation. In later segments, the inner cells of genital primordia cease to proliferate and adopt a compact distribution, and proliferative cells are also found in the testes primordia. Conclusions Proliferative cells have a characteristic localization and morphology throughout development from larva to adult of Mesocestoides corti, which is similar, and probably evolutionary conserved, to that described in other model cestodes. The characteristics of proliferative cells suggest that these consist of undifferentiated stem cells.